2010
DOI: 10.1103/physrevb.82.035401
|View full text |Cite
|
Sign up to set email alerts
|

Frictional duality of metallic nanoparticles: Influence of particle morphology, orientation, and air exposure

Abstract: The contact area dependence of the interfacial friction experienced during the translation of antimony nanoparticles deposited on a graphite substrate is studied under different conditions using the tip of an atomic force microscope as a manipulation tool. In vacuum a dual behavior of the friction-area curves is found, characterized by the observation that some particles exhibit friction below the detection limit while other similarly sized particles showed constant shear stress values. Detailed investigations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 50 publications
(65 reference statements)
4
30
1
Order By: Relevance
“…The slopes of the linear fits to the friction force data for Au NPs are 2.29 and 2.03 pN/nm 2 at a higher and lower F a , respectively. They exceed the values of 1.21 pN/nm 2 obtained in MD simulations for silver [7] and 1.04 pN/nm 2 from the experiments [3,5]. However, the experiments are performed at much lower sliding velocities than in the MD simulations, and the fact that the slope for the lower applied force is slightly smaller than for the higher force is consistent with a smaller slope at the AFM sliding velocities.…”
Section: -4contrasting
confidence: 44%
“…The slopes of the linear fits to the friction force data for Au NPs are 2.29 and 2.03 pN/nm 2 at a higher and lower F a , respectively. They exceed the values of 1.21 pN/nm 2 obtained in MD simulations for silver [7] and 1.04 pN/nm 2 from the experiments [3,5]. However, the experiments are performed at much lower sliding velocities than in the MD simulations, and the fact that the slope for the lower applied force is slightly smaller than for the higher force is consistent with a smaller slope at the AFM sliding velocities.…”
Section: -4contrasting
confidence: 44%
“…Very low friction was found in experiments with finite contacts at very low velocities to depend strongly on the orientation. 5,6 Coexisting states of very different friction have also been observed in the sliding of antimony nanoparticles 7,8 and have been attributed to contamination or (in)commensurate interfaces. Meanwhile, recent theoretical studies 9,10 have shown that nanocrystals can slide with constant orientation only for particular orientations.…”
Section: Introductionmentioning
confidence: 97%
“…To overcome a majority of these limitations, Ritter et al and Dietzel et al have pioneered a new approach in which the AFM tip is used to laterally manipulate antimony (Sb) nanoparticles, which have been thermally deposited on graphite and MoS 2 , forming atomically smooth interfaces with their substrates. [27][28][29][30][31] Thus, experimentally observed contact areas represent the real contact areas between the nanoparticles and the substrate, eliminating the need to distinguish between the apparent and real contact area, as it is usually the case for typical interfaces involving multiple asperities. 26 With the exception of the occasional observation of virtually vanishing friction due to structural lubricity under unusually clean conditions (almost exclusively ultrahigh vacuum), recording the lateral forces experienced by the AFM tip during the manipulation events has revealed a linear dependence of frictional force (F f ) on nanoparticle-substrate contact area (A) for the investigated size regimes (usually between 10 000 nm 2 to >100 000 nm 2 ).…”
Section: Introductionmentioning
confidence: 99%